2000
DOI: 10.1111/0033-0124.00207
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Conservation Reserve Programs and Land ‘Slippage’ in Southwestern Kansas

Abstract: Historically land reserve programs have been used to reduce soil erosion. Slippage, which occurs when the number of acres enrolled in a reserve program is not met by an equivalent reduction of acreage in production, has limited reserve success, however. This study addresses the effect of slippage on conservation reserves in southwestern Kansas from 1988-1994. Slippage has varied considerably on both spatial and temporal bases. At one extreme the programs were 100% successful in removing land from production, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…• lower than CRP acreage in crop production in 1982 (Table 1) • consistent with the 58 percent increase predicted by Roberts and Lubowski (2006) • consistent with the 50 to 80 percent reverse slippage rates suggested in prior research (Love andFoster 1990, Leathers andHarrington 2000) • consistent with the results of a 1993 survey that found that, if the CRP were not available, farmers would return 63 percent of their land to crop production (Osborn, Schnepf, andKeirn 1994, Dodson et al 1994).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…• lower than CRP acreage in crop production in 1982 (Table 1) • consistent with the 58 percent increase predicted by Roberts and Lubowski (2006) • consistent with the 50 to 80 percent reverse slippage rates suggested in prior research (Love andFoster 1990, Leathers andHarrington 2000) • consistent with the results of a 1993 survey that found that, if the CRP were not available, farmers would return 63 percent of their land to crop production (Osborn, Schnepf, andKeirn 1994, Dodson et al 1994).…”
Section: Resultssupporting
confidence: 81%
“…However, for a perspective on the effects of reverse slippage, one could assume that reverse slippage equals 100 minus the slippage rate. Most prior research has estimated slippage rates of 20 to 50 'percent (Love andFoster 1990, Leathers andHarrington 2000). Thus one might assume that reverse slippage rates range from 50 to 80 percent.…”
mentioning
confidence: 99%
“…Externality An agent's activity affects the welfare of other agents who do not intend to bear the burden or receive the benefit (Pigou, 1920;Buchanan & Stubblebine, 1962) Positive externalities with forest ecosystem services (Glück, 2000) Negative externalities with pollution (Henderson, 1977) Leakage When a policy action in a jurisdiction leads to the relocation or diffusion of some production and associated economic and environmental outcomes to other jurisdictions (Felder & Rutherford, 1993;Paltsev, 2001) Carbon (Babiker 2005) Forest conservation (Gan & McCarl, 2007) Biodiversity conservation (Ewers & Rodrigues, 2008) Land use (Lambin & Meyfroidt, 2011) Spillover effect Used as a synonym for leakage and externality (Aukland et al, 2003;Buchanan & Stubblebine, 1962) Timber (Wear & Murray, 2004) Land use policy (Hyde, Amacher, & Magrath, 1996) Slippage effect Often used as a synonym for leakage and indirect land use change (Leathers & Harrington, 2000;Wu, 2000) Agricultural land conservation (Flemming, 2014) Forest conservation (Alix-Garcia et al, 2012)…”
Section: Terminology Description Key Examplesmentioning
confidence: 99%
“…For example, approximately 63% of land that left the program by 1997 was returned to crop production and another 31% was used for livestock grazing (Sullivan et al, 2004). In some areas, slippage, an unintended consequence of land use policy, may have occurred as farmers opened up new areas for cultivation to replace other lands that were enrolled in the CRP; although, slippage may have primarily occurred at the start of the CRP program rather than with later enrollment or renewals (Leathers and Harrington, 2000). A few ecoregions had small net increases in agriculture, although it had little effect on the overall direction of land-cover change in the Plains.…”
Section: Tablementioning
confidence: 99%